Comparison of Erythrocyte Index Values of Venous and Capillary Blood : Perbandingan Nilai Indeks Eritrosit pada Darah Vena dan Kapiler - Wahyuni, Nining; Aliviameita, Andika (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Erythrocyte index is a laboratory examination in establishing the diagnosis of anemia including MCV, MCH, and MCHC obtained from the calculation of hemoglobin, hematocrit, and the number of erythrocytes. This study aims to determine differences in the value of the erythrocyte index in venous and capillary blood. This research is an experimental laboratory study, the sample was examined at the Ar-Rahmah Tulangan Clinic in Sidoarjo in March 2020. The examination method used in this study was automatic. Blood samples were taken from 30 patients so that a total of 60 blood samples (30 venous blood and 30 capillary blood). The results of the examination with the Mann Withney test showed a significant difference in the value of MCV (p = 0.001) and MCH (p = 0.001) and there was no difference in the value of MCHC (p = 0.251).